Endobronchial Tuberculosis Mimicking Lung Malignancy: A Case Report - Riza Adi Saputra; Ira Nurrasyidah (Jurnal Respirasi, 2026)
Introduction: Endobronchial tuberculosis (EBTB) is an infection of Mycobacterium tuberculosis (MTB) in the tracheobronchial tree. This case report aimed to describe the diagnostic challenge of endobronchial TB mimicking lung malignancy and to emphasize the role of bronchoscopy in establishing the diagnosis. Case: A 28-year-old male complained of a dry cough and weight loss for 4 months and had a lump on the left side of his back and neck for 3 months. Lung palpation found decreased fremitus, dull percussion, and decreased vesicular breath sounds in the middle-left lung. Acid-fast bacilli (AFB) sputum was negative, and the finding of the lump from the fine needle aspiration biopsy (FNAB) was chronic inflammation. Chest X-ray (CXR) showed an irregular border and homogeneous opacity in the left middle lung field. Chest computed tomography (CT) suggested a lung mass with a perihilar-left peribronchial infiltrative solid lesion and enlarged subcarinal and peribronchial lymph nodes. Bronchoscopy revealed easily bleeding leukoplakia in the left upper lobe bronchus; forceps biopsy: nucleic acid amplification test (NAAT) MTB detected at very low levels, without rifampicin resistance. Malignant cells were not detected from brushing cytology and bronchoalveolar lavage (BAL). Finally, the patient was diagnosed with EBTB and received 6 months of anti-TB therapy. Conclusion: Bronchoscopy has a higher biopsy sensitivity than FNAB in diagnosing EBTB. The bronchoscopy results in this case indicated an active caseous type. Endobronchial TB therapy uses a standard anti-TB combination for 6-9 months, aiming to eradicate and prevent tracheobronchial stenosis. Hence, there needs to be early diagnosis. This patient showed clinical and radiological improvement after 6 months of therapy. In this case, bronchoscopy was significant for diagnosing EBTB.